Induction of autoantibodies against lung matrix proteins and smoke-induced inflammation in mice - Hylkema Machteld N; Postma Dirkje S; Jekel Henrike; Geerlings Marie; Timens Wim; Brandsma Corry-Anke; Kerstjens Huib AM (BMC Pulmonary Medicine, 2010)
Abstract Background Smoking is the major etiologic factor in COPD, yet the exact underlying pathogenetic mechanisms have not been elucidated. Since a few years, there is mounting evidence that a specific immune response, partly present as an autoimmune response, contributes to the pathogenesis of COPD. Increased levels of anti-Hep-2 epithelial cell and anti-elastin autoantibodies as well as antibodies against airway epithelial and endothelial cells have been observed in COPD patients. Whether the presence of these autoantibodies contributes to the pathogenesis of COPD is unclear. Methods To test whether induction of autoantibodies against lung matrix proteins can augment the smoke-induced inflammatory response, we immunized mice with a mixture of the lung extracellular matrix (ECM) proteins elastin, collagen, and decorin and exposed them to cigarette smoke for 3 or 6 months. To evaluate whether the immunization was successful, the presence of specific antibodies was assessed in serum, and presence of specific antibody producing cells in spleen and lung homogenates. In addition, the presence of inflammatory cells and cytokines was assessed in lung tissue and emphysema development was evaluated by measuring the mean linear intercept. Results We demonstrated that both ECM immunization and smoke exposure induced a humoral immune response against ECM proteins and that ECM immunization itself resulted in increased macrophage numbers in the lung. The specific immune response against ECM proteins did not augment the smoke-induced inflammatory response in our model. Conclusions By demonstrating that smoke exposure itself can result in a specific immune response and that presence of this specific immune response is accompanied by an influx of macrophages, we provide support for the involvement of a specific immune response in the smoke-induced inflammatory response as can be seen in patients with COPD.